Índices plasmáticos de interleucina-6, força muscular e capacidade funcional em idosas da comunidade. - Daniela Matos Garcia Oliveira (2006)
The aging process occurs in an expressive way in Brazil and in the world. It is accompanied of an increase in the prevalence of degenerative chronic diseases and comorbidities, leading to a decline in physical functioning, in quality of life and in the autonomy of older persons. Age-related changes are peculiar and individual, occurring in many organs and systems. The dysfunction of the immune system related to the age is denominated immunosenescence whereas the alterations in the muscular system are named sarcopenia. Sarcopenia as loss of muscle mass and strength related to ageing, independently of coexisting diseases. Sarcopenia has multifactorial origin and has a great impact at physical functioning. Nowadays sarcopenia is being related to the immunosenescence process, mainly to increase in inflammatory mediators, such as for interleukin-6 levels. The present study had the general objective, of investigating the relationship between interleukin-6 levels with the measures of muscular force and of functional capacity in older women living in community. A correlational research was accomplished with 57 older women living in Belo Horizonte, Brazil, where Interleukin-6 levels were measured by ELISA, flexion and extension knee muscle strength were assessed by isokinetic dynamometer and physical function was assessed by timed by timed chair rise and by maximal and habitual gait speed. For characterization of the sample, descriptive analysis was used , and for verification of variables skewness, Shapiro-Wilk test had been used. Correlation between interleukin-6 levels, muscle strength and physical function was verified by Spearman correlation coefficient. Age was categorized and its association with interleukin-6 levels was done by Kruskal-Wallis test and association between age categorized and interleukin-6 categorized was done by chi-square test. Post Hoc analysis was done by Dunn test. The results shows significant inverse correlation between interleukin-6 levels (mean 1,95 + 1,77 pg/ml) and muscle strength seen as work for body weight for quadriceps (r = -0,315; p = 0,017) and hamstrings (r = -0,265; p = 0,047) muscles, in extension (mean 142,21%) and flexion (median 70,70%) of knee, respectively. Functional tests did not show significant correlation with interleukin-6 levels. In all analysis was considered an = 0,05. This study results show an inverse correlation between interleukin-6 and muscle strength in community older women, suggesting that high interleukin-6 levels are correlated with decreased muscle strength. This study indicates the need of comprehension by physical therapists about silent action of inflammatory mediators on muscles, and for the importance of exercise interventions for reducing interleukin-6 levels.